Methodological Pluralism in Business and Information Systems Engineering? - Loos, Peter; Mettler, Tobias; Winter, Robert; Goeken, Matthias; Frank, Ulrich; Winter, Alfred (Business & Information Systems Engineering, 2013)
This article is also available in German in print and via http://www.wirtschaftsinformatik.de: Loos P (2013) Methodenpluralismus in der Wirtschaftsinformatik? WIRTSCHAFTSINFORMATIK. doi:  10.1007/s11576-013-0392-0.